Ответ:
Пошаговое объяснение:
1) 2x+2=-3
2x=-3-2
2x=-5
x= -5/2
x = -2.5
2) 2x-3*(7+2x)=11
2x -21 -6x=11
-4x=11+21
-4x=32
x= -8
-2,5
-8
2х +2=-3
2х=-3-2
2х=-5
х=-5÷2
х= -2,5
2х-3(7 + 2х) = 11
2х - 21 - 6х = 11
2х-6х=11+21
-4х=32
х=32÷-4
х=-8
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
1) 2x+2=-3
2x=-3-2
2x=-5
x= -5/2
x = -2.5
2) 2x-3*(7+2x)=11
2x -21 -6x=11
-4x=11+21
-4x=32
x= -8
Ответ:
-2,5
-8
Пошаговое объяснение:
2х +2=-3
2х=-3-2
2х=-5
х=-5÷2
х= -2,5
2х-3(7 + 2х) = 11
2х - 21 - 6х = 11
2х-6х=11+21
-4х=32
х=32÷-4
х=-8